2018
DOI: 10.1016/j.hydromet.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ruthenium by solvent extraction and direct electrodeposition using ionic liquid solution

Abstract: It is important to recover Ru metal from spent target materials including Pt, Co and Cr. The extraction behavior using Di-(2-ethylhexyl)phosphoric acid (HDEHP) and ionic liquid (IL), triethyl-n-pentyl phosphonium bis(trifluoromethylsulfonyl)amide ; [P2225][TFSA] diluent was investigated with pH dependence. Co(II) and Cr(II) were selectively extracted into the organic phase because the extraction of Co(II) and Cr(II) proceeded by cation exchange. As a result, Pt(IV) and Ru(III) can be separated from Co(II) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In the last decade, electrodeposition has been widely used for the purification and separation of metal ions. Many studies have reported the recovery of metals such as Cu, 22 Sr, 23 U, 24 Pt, 25 and Ru 26 through solvent extraction–direct electrodeposition. Compared with the conventional organic phase back-extraction method, direct electrodeposition can reduce the use of volatile organic solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, electrodeposition has been widely used for the purification and separation of metal ions. Many studies have reported the recovery of metals such as Cu, 22 Sr, 23 U, 24 Pt, 25 and Ru 26 through solvent extraction–direct electrodeposition. Compared with the conventional organic phase back-extraction method, direct electrodeposition can reduce the use of volatile organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, electrodeposition has been widely used for the purification and separation of metal ions. Many studies have reported the recovery of metals such as Cu, 22 Sr, 23 U, 24 Pt, 25 and Ru 26 1a). The characteristic UV−Vis absorption peaks of Pd(II) aqueous solution appeared at 222 and 280 nm (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the electrodeposition study in only ionic liquid medium, there are few reports dealing with the feasibility of direct electrodeposition from the ligand/IL mixture. 61,62,65,66 The authors have claimed different deposition potentials depending on the nature of ionic liquid and the feed acidity used. A schematic of the direct electrodeposition of the metal ion from the ligand containing IL phase is shown in Fig.…”
Section: Feasibility Of Electrodeposition From Ligand/il Phasementioning
confidence: 99%
“…From the standpoint of recovery, this combination method has several advantages such as simple construction, less secondary waste, and easy handling. We demonstrated the recovery of In [14], Fe [15], and Ru [16] by the combination of solvent extraction and direct electrodeposition using phosphonium-based ILs. However, the recovery of Pt metal by the extractionelectrodeposition method has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%